How best to structure interdisciplinary primary care teams: the study protocol for a systematic review with narrative framework synthesis. Issue 1 (December 2016) - Wranik, W.; Hayden, Jill; Price, Sheri; Parker, Robin; Haydt, Susan; Edwards, Jeanette; Suter, Esther; Katz, Alan; Gambold, Liesl; Levy, Adrian
Abstract Background Western publicly funded health care systems increasingly rely on interdisciplinary teams to support primary care delivery and management of chronic conditions. This knowledge synthesis focuses on what is known in the academic and grey literature about optimal structural characteristics of teams. Its goal is to assess which factors contribute to the effective functioning of interdisciplinary primary care teams and improved health system outcomes, with specific focus on (i) team structure contribution to team process, (ii) team process contribution to primary care goals, and (iii) team structure contribution to primary care goals. Methods and design The systematic search of academic literature focuses on four chronic conditions and co-morbidities. Within this scope, qualitative and quantitative studies that assess the effects of team characteristics (funding, governance, organization) on care process and patient outcomes will be searched. Electronic databases (Ovid MEDLINE, Embase, CINAHL, PAIS, Web of Science) will be searched systematically. Online web-based searches will be supported by the Grey Matters Tool. Studies will be included, if they report on interdisciplinary primary care in publicly funded Western health systems, and address the relationships between team structure, process, and/or patient outcomes. Studies will be selected in a three-stage screening process (title/abstract/full text) by two independent reviewers in each stage. Study quality will be assessed using the Mixed Methods Assessment Tool. An a priori framework will be applied to data extraction, and a narrative framework approach is used for the synthesis. Discussion Using an integrated knowledge translation approach, an electronic decision support tool will be developed for decision makers. It will be searchable along two axes of inquiry: (i) what primary care goals are supported by specific team characteristics and (ii) how should teams be structured to support specific primary care goals? The results of this evidence review will contribute directly to the design of interdisciplinary primary care teams. The optimized design will support the goals of primary care, contributing to the improved health of populations. Systematic review registration PROSPEROCRD42016041884